1995
DOI: 10.7326/0003-4819-122-10-199505150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of External Forces to Left Ventricular Diastolic Pressure: Implications for the Clinical Use of the Starling Law

Abstract: A substantial proportion of measured resting left ventricular diastolic pressure stems from forces extrinsic to the left ventricle rather than from diastolic stiffness in the left ventricle itself. This markedly influences the dependence of cardiac output on filling pressure and has important implications for clinical application of the Starling law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 0 publications
8
41
0
1
Order By: Relevance
“…25 In patients with CHF, marked external constraint to LV filling was present in the majority of patients with LVEDP/pulmonary capillary wedge pressure Ͼ15 mm Hg. 14,26 In accordance with our hypothesis, LV pacing significantly reduced this external constraint, presumably by causing a phase shift in LV filling relative to RV filling, as recently demonstrated in the LV pacing canine model, 17 in which LV relaxation and filling occurred relatively early compared with RV relaxation and filling. If so, RV diastolic pressure and pericardial pressure are likely to be lower at any given LV diastolic volume.…”
Section: Bleasdale Et Al LV Pacing Reduces Ventricular Interactionsupporting
confidence: 72%
See 1 more Smart Citation
“…25 In patients with CHF, marked external constraint to LV filling was present in the majority of patients with LVEDP/pulmonary capillary wedge pressure Ͼ15 mm Hg. 14,26 In accordance with our hypothesis, LV pacing significantly reduced this external constraint, presumably by causing a phase shift in LV filling relative to RV filling, as recently demonstrated in the LV pacing canine model, 17 in which LV relaxation and filling occurred relatively early compared with RV relaxation and filling. If so, RV diastolic pressure and pericardial pressure are likely to be lower at any given LV diastolic volume.…”
Section: Bleasdale Et Al LV Pacing Reduces Ventricular Interactionsupporting
confidence: 72%
“…26 This acute reduction in RV volume removes external constraint to LV filling from the RV and pericardium. During this intervention, LVEDP was progressively reduced over several beats.…”
Section: Bleasdale Et Al LV Pacing Reduces Ventricular Interactionmentioning
confidence: 99%
“…These effects are further amplified during exercise where increased preload, further elevations in filling pressures and impaired reduction of afterload (due to a blunted vasodilator response to exercise) collectively contribute to exercise intolerance [44,45,47]. Exercise-induced elevation of pulmonary artery pressure and the ensuing elevation of right-sided pressures may contribute to poor functional capacity secondary to ventricular interdependence and increased pericardial constraint [43,89,90]. Lam et al [91] have recently shown that pulmonary hypertension may be present in up to 83% of HFpEF patients and found strong association between the severity of pulmonary hypertension and mortality.…”
Section: Venrticular-arterial Coupling and Endothelial Dysfunctionmentioning
confidence: 99%
“…However, in the present study, we applied a modified approach by continuously measuring LV pressure and volume during occlusion of the inferior vena cava to reduce RV volume and pressure for the short term. 22 This short-term reduction in RV volume removes external constraint to LV filling from the RV and pericardium. In the present study, we confirm that at least part of the short-term hemodynamic benefit of CRT in this population is due to a reduction in external constraint to LV filling.…”
Section: Discussionmentioning
confidence: 99%